2018
DOI: 10.1242/dev.164640
|View full text |Cite
|
Sign up to set email alerts
|

SLAM-ITseq: Sequencing cell type-specific transcriptomes without cell sorting

Abstract: Cell type-specific transcriptome analysis is an essential tool for understanding biological processes in which diverse types of cells are involved. Although cell isolation methods such as fluorescence-activated cell sorting (FACS) in combination with transcriptome analysis have widely been used so far, their time-consuming and harsh procedures limit their applications. Here, we report a novel in vivo metabolic RNA sequencing method, SLAM-ITseq, which metabolically labels RNA with 4-thiouracil in a specific cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…A reduced conversion rate is likely to worsen sensitivity. Finally, methods based on RNA metabolic labeling cannot be readily applied to model organisms, mammals (Matsushima et al 2018) or plants (Sidaway-Lee et al 2014), in vivo.…”
Section: Experimental and Computational Pitfalls Of Rna Metabolic Labmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced conversion rate is likely to worsen sensitivity. Finally, methods based on RNA metabolic labeling cannot be readily applied to model organisms, mammals (Matsushima et al 2018) or plants (Sidaway-Lee et al 2014), in vivo.…”
Section: Experimental and Computational Pitfalls Of Rna Metabolic Labmentioning
confidence: 99%
“…Despite their advantages and popularity, methods based on RNA metabolic labeling are affected by various pitfalls, especially when a limited amount of nascent RNA is produced and when aiming at studying very short responses (Baptista and Dölken 2018). Moreover, these methods cannot be readily applied to model organisms, be it mammals (Matsushima et al 2018) or plants (Sidaway-Lee et al 2014), in vivo. For all these reasons, being able to study RNA dynamics from just total RNA would be a valuable alternative.…”
mentioning
confidence: 99%
“…I envision that the combination of multiple autochthonous models in parallel and scRNA-seq and BS-seq may be exploited to evaluate the way the core tumor and in the infiltrating margins respond to individual treatments. Importantly, metabolic labeling of RNA in vivo now enables identifying faster and more accurately the adaptive transcriptional changes ( 173 ).…”
Section: Experimental Models For High-grade Gliomasmentioning
confidence: 99%
“…A major limitation of sci-fate is that S4U labeling experiments are generally performed in vitro. 33 However, recent studies have shown that S4U can be used in conjunction with transgenic UPRT- 34 expressing mice to stably label cell type-specific nascent RNA transcription in vivo [62][63][64] , suggesting that All cell lines (A549, HEK293T and NIH/3T3 cells) were trypsinized, spun down at 300xg for 5 min (4°C) 12 and washed once in 1X ice-cold PBS. All cells were fixed with 4ml ice cold 4% paraformaldehyde (EMS) 13 for 15 min on ice.…”
mentioning
confidence: 99%